Diet and rosacea: the role of dietary change in the management of rosacea - Weiss, Emma (Dermatol Pract Concept, 2017)
Dietary change may play a role in the therapy of rosacea. Certain foods and beverages may act as “triggers” for rosacea exacerbations. These may be divided into heat-related, alcohol-related, capsaicin-related, and cinnamaldehyde-related. One potential pathogenic mechanism may be via the activation of transient receptor potential cation channels, which result in neurogenic vasodilatation. Further research is needed on the role of the gut skin connection in rosacea. Epidemiologic studies suggest that patients with rosacea have a higher prevalence of gastrointestinal disease, and one study reported improvement in rosacea following successful treatment of small intestinal bacterial overgrowth. While further research is required in this area, patients may be advised on measures to support a healthy gut microbiome, including the consumption of a fiber-rich (prebiotic) diet.